Role of closed intramedullary interlocking nailing in comminuted fractures of long bones in lower limbs - Sreen, Sanjeev; Daroch, Manjit S.; Vashisht, Deepak; Kapil, Nitish (International Journal of Research in Medical Sciences, 2017)
Background: Fractures are the most common form of skeletal injuries encountered in orthopaedic practice. Increase in mechanization and high-speed travel are accompanied by increase in the number and severity of the fracture. Our ultimate goal of femur and tibia fracture management is restoration of alignment, rotation and length, preservation of blood supply to aid union, prevention of infection and early rehabilitation of the patient. Methods: 30 adult patients of either sex with 30 comminuted fractures of long bones were treated with closed intramedullary interlocking nail. AO type B3 and C in femur and tibia are included. There were 25 males and 5 females, and average age of patients was 36.2 years. Out of 30 cases, 13 cases were of femur fracture while 17 cases were of tibia fracture. There were 21 closed and 9 patients had Grade I open fractures. Results: Closed intramedullary interlocking nailing was done in 13 cases of femur fracture and 17 cases of tibia fracture. The average duration of partial weight bearing in femur fractures was 4.85 weeks and in tibia fractures was 5.53 weeks. 20 fractures united without additional intervention. The average duration of radiological union in femur fractures was 18.65 weeks and for tibia fractures was 19.29 weeks. Conclusions: Closed intramedullary interlocking nailing is the treatment of choice of comminuted fractures of long bones in lower limbs which cause minimum damage to the blood supply of the fracture fragments which promotes the chances of bone union.